Professional quality of life and burnout amongst radiation oncologists: The impact of alexithymia and empathy. (June 2020) - Franco, Pierfrancesco; Tesio, Valentina; Bertholet, Jenny; Gasnier, Anne; Gonzalez del Portillo, Elisabet; Spalek, Mateusz; Bibault, Jean-Emmanuel; Borst, Gerben; Van Elmpt, Wouter; Thorwarth, Daniela; Mullaney, Laura; Røe Redalen, Kathrine; et al.
Highlights: Burnout is a critical issue with an impact on quality of life and performance at work. Alexythymia and empathy are personality traits affecting the individual capacity to cope with stress. Alexythymia increases the risk of burnout with a negative impact on professional quality of life. Empathy leads to higher levels of acute stress, but does not automatically lead to burnout. This data may help in identifying subjects at risk to implement preventive strategies. Abstract: Background and purpose: Different factors may influence the professional quality of life of oncology professionals. Among them, personality traits, as alexithymia and empathy, are underinvestigated. Alexithymia is about deficits in emotion processing and awareness. Empathy is the ability to understand another's 'state of mind'/emotion. The PROject on BurnOut in RadiatioN Oncology (PRO BONO) assesses professional quality of life, including burnout, in the field of radiation oncology and investigates alexithymia and empathy as contributing factors. Material and methods: An online survey was conducted amongst ESTRO members. Participants completed 3 validated questionnaires for alexithymia, empathy and professional quality of life: (a) Toronto Alexithymia Scale; (b) Interpersonal Reactivity Index; (c) Professional Quality of Life Scale. The present analysis, focusing on radiation/clinical oncologists, evaluates Compassion Satisfaction (CS), Secondary Traumatic Stress (STS) and Burnout and correlates them with alexithymia and empathy (empathic concern, perspective taking and personal distress) with generalized linear modeling. Significant covariates on univariate linear regression analysis were included in the multivariate linear regression model. Results: A total of 825 radiation oncologists completed all questionnaires. A higher level of alexithymia was associated to decreased CS ( β : −0.101; SE: 0.018; p  < 0.001), increased STS ( β : 0.228; SE: 0.018; p  < 0.001) and burnout ( β : 0.177; SE: 0.016; p  < 0.001). A higher empathic concern was significantly associated to increased CS ( β : 0.1.287; SE: 0.305; p  = 0.001), STS ( β : 0.114; SE: 0.296; p  < 0.001), with no effect on burnout. Personal distress was associated to decreased CS ( β : −1.423; SE: 0.275; p  < 0.001), increased STS ( β : 1.871; SE: 0.283; p  < 0.001) and burnout ( β : 1.504; SE: 0.245; p  < 0.001). Conclusions: Alexithymic personality trait increased burnout risk, with less professional satisfaction. Empathic concern was associated to increased stress, without leading to burnout, resulting in higher professional fulfillment. These results may be used to benchmark preventing strategies, such as work-hour restrictions, peer support, debriefing sessions, and leadership initiatives for professionals at risk.